The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/1755-6783.133708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and etiology of sexually transmitted infections in a gynecologic unit of a developing country

Abstract: Background: Despite enormous sensitization and management options available for sexually transmitted infections (STIs) in the last 2 decades, these infections remain highly endemic in certain parts of Cameroon. This is a descriptive study of genital hygiene and predisposition to STIs in some women in Dschang, West Region, Cameroon. Materials and Methods: A total of 2172 consenting women seeking gynecological care at the Dschang District Hospital from 2009 to 2010 were interviewed, examined, cervical/blood spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…Women who practiced douching had a significantly higher prevalence of BV (χ 2 = 23.935, P = 0.001) than those who were not douching similar to reports from elsewhere [36]. Previous studies in Cameroon have also reported douching as a common practice among women [6, 26], as they believe that thorough bathing must involve douching. This is appalling considering the high level of education of participants: 36.9% secondary, 29.1% higher education.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Women who practiced douching had a significantly higher prevalence of BV (χ 2 = 23.935, P = 0.001) than those who were not douching similar to reports from elsewhere [36]. Previous studies in Cameroon have also reported douching as a common practice among women [6, 26], as they believe that thorough bathing must involve douching. This is appalling considering the high level of education of participants: 36.9% secondary, 29.1% higher education.…”
Section: Discussionsupporting
confidence: 74%
“…Nsagha et al [25] reported a similar prevalence in Yaounde, Cameroon but their study was on non-pregnant women. Our prevalence is higher than 24% reported by Kesah et al [26]. Findings of present study together with previous reports show that BV could be serious reproductive health concern among women in Cameroon.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation